Analysis of Capacity, Speed, and Degree of Saturation of Intersections and Roads - Isradi, Muhammad; Dwiatmoko, Hermanto; Setiawan, Muhammad Ikhsan; Supriyatno, Dadang (Yayasan Ahmar Cendekia Indonesia, 2020)
No traffic-signal intersection located on Jalan Serang and Jalan Curug, Tangerang Regency often causes traffic congestion. Many side barriers activities of vehicles inhibit the movement of traffic flow. The toll-road access, which is not far from the intersection, makes the queue long enough to enter Jl. Raya Serang also affects the performance of the surroundings. The study aims to determine the performance of the above intersection this time, which is measured by the capacity, degree of saturation, speed, queuing opportunities, density, and level of services. Field surveys and further analysis of the calculations that have been carried out show the intersection performance. The peak traffic volume occurred on Wednesday, February 5 2020, at 3877 pcu / hour at 07.00 - 08.00 WIB, with a capacity (C) of 2937 pcu / hour. From the available data, the DS value is 1.32. at the Service level F.